EFEK KOMBINASI XILO-OLIGOSAKARIDA DAN Lactobacillus casei DALAM MENGURANGI KADAR KOLESTEROL SECARA IN VITRO - Diani Sri Hidayati (JURNAL KEDOKTERAN, 2015)
Many studies reported that consumption of probiotics, prebiotics or combination of both (sinbiotics) can reduce cholesterol levels in the blood. Xilooligosaccharides has not clear yet to influence hipercholesterolemia. This study aimed to determine the xilooligosaccharides effeet against the Lactobacillus casei’s activity to reduce cholesterol levels in vitro. Lactobacillus casei is probiotic bacteria that was used as bacteria test in this study. This study was experimental laboratory with design was post test only control group design, samples in this study were Lactobacillus casei and xilooligosaccharides. Total samples 25 divided into five groups witch consist of K: as control (MRSB without L.casei and XOS), Pl :MRSB containing cholesterol + L. Casei, P2: MRSB containing cholesterol + L.casei + XOS 1%, P3: MRSB containing cholesterol + L,casei + XOS 3 %, P4: MRSB containing cholesterol + L.casei + XOS 5%. The results of this study showed that the lowest reduction cholesterol levels was P1 group whose not given the xos (12,42±1,29 µg/ml), then P2 group whose given 1% concentration of XOS (13,15±1,87 µg/ml), then P3 group whose given 3% concentration of XOS ( l4,45+1,53 µg/ml), then the highest reduction was P4 group whose given 5% concentration of XOS (16,40 ± 1,85 µg/ml). This showed that XOS affected L. casei's activity to reduce cholesterol levels. Anova analytic results showed significant differences ( p=-0,008), then post hoc tests with LSD showed significant differences between the P4 with P1 (p=0,002), and P2 between P4 (p=0,007), while between the other group showed no significant differences.